A REVIEW ARTICLE ON: ANTIBIOTIC RESISTANCE - Ajid K. Mule; Suraj Malpani; Nemane, Shradha T.; Sushil S. Kore; Ayaj S. Pathan (Journal of Biomedical and Pharmaceutical Research, 2020)
Antibiotics are the ‘wonder drugs’ to combat microbes. For decades, various types of antibiotics have not only been used for therapeutic purposes but practiced prophylactically across other industries such as agriculture and animal husbandry. Antibiotic-resistant infections correlate with the level of antibiotic consumption. Non-judicial use of antibiotics is one of the reason for making the microbes resistant. The antibiotic therapy store for emerging hard-to-treat multidrug-resistant bacterial infections is limited, resulting in high morbidity and mortality report. As per the World Health Organization “First worldwide Report on Antibiotic Resistance”, and the U.S. Centers for Disease Control & Prevention (CDC&P) and the spread of “superbugs” - bacteria that have changed in ways that provided antibiotics non effective against them - is a severe and growing threat around the world. Once common treatments for not only everyday intestinal and urinary tract infections but also pneumonia as well as infections in newborn and diseases like gonorrhea are no longer working in people. Thus, in 2013, two million people in the U.S. were affected by antibiotic-resistant bacteria, and 23,000 of them die each year as a result. Keywords: Wonder drugs, antibiotic resistance, CDC&P, Superbugs etc.